2016
DOI: 10.1177/1073191116660381
|View full text |Cite
|
Sign up to set email alerts
|

Externalizing Behavior Across Childhood as Reported by Parents and Teachers: A Partial Measurement Invariance Model

Abstract: The externalizing spectrum may explain covariation among externalizing disorders observed in childhood and adulthood. Few prospective studies have examined whether externalizing spectrum might manifest differently across time, reporters, and gender during childhood. We used a multitrait, multimethod model with parent and teacher report of attention-deficit/hyperactivity disorder (ADHD) symptoms, oppositional defiant disorder (ODD) symptoms, and conduct disorder (CD) symptoms from kindergarten to Grade 5 in dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 74 publications
3
20
0
3
Order By: Relevance
“…There are two possible explanations for these findings. The first is that boys tend to show more externalized behavior early in their development, as early as the preschool years (Broidy et al, 2003; King et al, 2018), and this may test parents’ abilities more so than for girls. Support for this hypothesis comes from studies that have examined foster placement stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two possible explanations for these findings. The first is that boys tend to show more externalized behavior early in their development, as early as the preschool years (Broidy et al, 2003; King et al, 2018), and this may test parents’ abilities more so than for girls. Support for this hypothesis comes from studies that have examined foster placement stability.…”
Section: Discussionmentioning
confidence: 99%
“…The association between CM and parenting may also be moderated by child gender. Some studies have shown that parenting behavior differs as a function of child gender (Leaper, Anderson, & Sanders, 1998; Shanahan, McHale, Crouter, & Osgood, 2007), and in light of the frequently documented association between child gender and externalizing behavior (King et al, 2018), it is possible that boys would more often elicit more controlling or otherwise negative parental behaviors from their parents, possibly increasing the CM–parental behavior association (Cross et al, 2016). Indirect support of this possibility comes from the observation that boys are more often exposed to emotional and physical abuse than girls (Government of Canada, 2012).…”
Section: Empirical Overview Of Child Maltreatment History and Parentimentioning
confidence: 99%
“…Less research has been done to define the psychometrics of behavioural tests of impulsivity (Bari & Robbins, 2013; Perales et al., 2009), but studies have shown moderate to good test-retest reliability of the Go/No-Go task and an association between performance on the task and other executive-functioning tests or measures of psychopathology, e.g. teacher ratings of ADHD symptoms (Kuntsi et al., 2005; Langenecker et al., 2007).…”
Section: Methodsmentioning
confidence: 99%
“…For example, intervention or experimental psychopathology researchers might mix experimental methods with longitudinal data analytic methods to study how treatment effects or psychopathology unfolds over both short (Tang, Beberman, DeRubeis, & Pham, 2005) and long (Laurenceau, Hayes, & Feldman, 2007) periods of time. Researchers who study psychopathology might use structural equation (King, Luk, et al, 2018), latent class (Witkiewitz et al, 2013) or network analysis (Borsboom, Cramer, Schmittmann, Epskamp, & Waldorp, 2011) to study the structure of psychopathology, or use longitudinal models (King, Littlefield, et al, 2018) to study how psychopathology changes over time. Many clinical researchers must use methods that account for nesting of observations within clusters (such as multiple observations of the same people, or multiple clients nested within providers nested within organizations) (McNeish, Stapleton, & Silverman, 2016).…”
Section: Implementation Science Of Quantitative Methodsmentioning
confidence: 99%